Web Scraping Situs Berita Menggunakan Bahasa Pemograman Python - Fikri, Muhammad Ramadan; Handayanto, Rahmadya Trias; Irwan, Dadan (Program Studi Informatika Fakultas Ilmu Komputer Universitas Bhayangkara Jakarta Raya, 2022)
Currently the rapid development of technology provides innovation, one of which is the technique of obtaining information from portal websites, termed web scrapers. This application provides data needs in the form of information where the process of retrieving information from sites will later be taken to observe behavior and perceptions to get the right segmentation. Most data collection is currently still done manually, as a result, this method has several system limitations, namely the length of the data collection process so that it slows down the performance of market segment analysis. The risk is not getting the right market segmentation. To solve this problem, a web scraping news site is needed. In this study, web scraping news sites were created using the python programming language and the flask library to display web scraping. In addition, the Selenium library is used to simplify application creation, facilitate interaction with the web and provide facilities to control a web browser. This program can retrieve data based on keywords, where the results are in the form of the title, posting date, summary, then collect the data that has been taken into a csv file extension automatically.